HPV in cepljenje - Pavlova, Ljupka (Placebo, 2025)
Human papillomaviruses (HPV) are the most common sexually transmitted viruses and play a key etiological role in the development of cervical, anogenital, and oropharyngeal cancers. HPV vaccination represents one of the most significant achievements in modern preventive medicine. This article provides a comprehensive overview of prophylactic HPV vaccines, covering immunological mechanisms, clinical efficacy, and population-level impact, as well as access barriers, social determinants of health, and the future of mRNA and therapeutic vaccine technologies. Special focus is placed on the role of pharmacists in expanding access and the necessity of equitable global implementation. The elimination of cervical cancer as a public health problem is an achievable goal—one that requires the integration of science, communication, and justice.
Keywords: cepljenje; cervical cancer; HPV; human papilloma virus; Humani papilomavirus; immunization; mRNA cepiva; mRNA vaccines; rak materničnega vratu